2012
DOI: 10.1182/blood-2011-09-380709
|View full text |Cite
|
Sign up to set email alerts
|

CLEC-2 and Syk in the megakaryocytic/platelet lineage are essential for development

Abstract: The C-type lectin receptor CLEC-2 signals through a pathway that is critically dependent on the tyrosine kinase Syk. We show that homozygous loss of either protein results in defects in brain vascular and lymphatic development, lung inflation, and perinatal lethality. Furthermore, we find that conditional deletion of Syk in the hematopoietic lineage, or conditional deletion of CLEC-2 or Syk in the megakaryocyte/platelet lineage, also causes defects in brain vascular and lymphatic development, although the mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
139
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(153 citation statements)
references
References 50 publications
10
139
3
Order By: Relevance
“…Some groups have reported that platelet activation by CLEC2 signaling may regulate LEC growth in vitro through secretion of platelet granule contents (6,10). However, we have not observed such effects on LEC growth in vitro or detected major defects in the pattern or rate of lymphatic vascular development in vivo (8,11), and how such an angiogenic mechanism would explain an ongoing requirement in mature, presumably nonangiogenic, animals is not clear.…”
Section: Introductioncontrasting
confidence: 46%
See 2 more Smart Citations
“…Some groups have reported that platelet activation by CLEC2 signaling may regulate LEC growth in vitro through secretion of platelet granule contents (6,10). However, we have not observed such effects on LEC growth in vitro or detected major defects in the pattern or rate of lymphatic vascular development in vivo (8,11), and how such an angiogenic mechanism would explain an ongoing requirement in mature, presumably nonangiogenic, animals is not clear.…”
Section: Introductioncontrasting
confidence: 46%
“…Mice deficient in PDPN, CLEC2, or the CLEC2 signaling proteins SYK and SLP-76 exhibit blood-filled lymphatics during fetal life and die shortly after birth due to defective lymphatic function (3)(4)(5)(6). Tissue-specific deletion experiments reveal that CLEC2 and its intracellular signaling effectors are required in platelets, while PDPN is required in endothelial cells to prevent this phenotype (4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…So it appears that CLEC-2-dependent functions of Pdpn are involved wherever there is a connection between blood and lymphatic vessels. It was reported that platelets might inhibit LEC function (39,40). Whether this is a direct effect via Pdpn-mediated changes in LECs, or an indirect effect due to a soluble factor (i.e.…”
Section: Mpdpnt34a-fc As An Improved Lymphangiogenesis Inhibitormentioning
confidence: 99%
“…Mice-Platelet specific CLEC-2 knock-out mice were produced as described previously (50). Briefly, the CLEC-2 gene (CLEC1b) was flanked with LoxP sites, and this mouse was cross-bred with a PF4-Cre expressing mouse to drive excision of the gene in only the megakaryocyte/platelet lineage.…”
Section: Methodsmentioning
confidence: 99%